2016
DOI: 10.1007/s12975-016-0506-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage

Abstract: Brain edema following intracerebral hemorrhage (ICH) causes severe secondary brain injury, and no efficient pharmacological preventions are available. The present study was designed to demonstrate the neuroprotective effects of glibenclamide on brain edema and key factors of the blood-brain barrier (BBB). The study was divided into two parts. First, we utilized an autoblood-induced rat model to investigate the expression of sulfonylurea receptor 1 (Sur1). Second, rats were randomized into sham, vehicle, and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 57 publications
3
98
2
4
Order By: Relevance
“…In addition to its hypoglycemic effects, glibenclamide has been shown to play a protective role in inflammation‐related disorders, particularly in CNS injury, including traumatic brain injury (Patel, Gerzanich, Geng, & Simard, ; Xu et al, ), ischemia‐reperfusion injury (Abdallah, Nassar, & Abd‐El‐Salam, ; Caffes et al, ; Gao et al, ; Yang et al, ), subarachnoid hemorrhage (SAH) (Simard et al, ; Tosun et al, ), and ICH (Jiang et al, ; Ma et al, ). Glibenclamide significantly attenuates neuroinflammation, decreases disruption of the BBB, and improves memory function by blocking the Sur1–Trpm4 channel in both experimental SAH and ICH (Zhou, Shi, Wang, Chen, & Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its hypoglycemic effects, glibenclamide has been shown to play a protective role in inflammation‐related disorders, particularly in CNS injury, including traumatic brain injury (Patel, Gerzanich, Geng, & Simard, ; Xu et al, ), ischemia‐reperfusion injury (Abdallah, Nassar, & Abd‐El‐Salam, ; Caffes et al, ; Gao et al, ; Yang et al, ), subarachnoid hemorrhage (SAH) (Simard et al, ; Tosun et al, ), and ICH (Jiang et al, ; Ma et al, ). Glibenclamide significantly attenuates neuroinflammation, decreases disruption of the BBB, and improves memory function by blocking the Sur1–Trpm4 channel in both experimental SAH and ICH (Zhou, Shi, Wang, Chen, & Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, glibenclamide was suggested to effectively inhibit inflammatory cells migration by inhibiting NLRP3 inflammasome assembly, thereby reducing inflammatory cells infiltration and preventing further organ damage in ischemic tissue (Gao et al, ; Satoh, Kambe, & Matsue, ). One study demonstrated that glibenclamide protects BBB integrity, which reduces the extravasated protein‐induced production of proinflammatory mediators and improves neurological outcomes after experimental ICH (Jiang et al, ). Therefore, we tested the hypothesis that glibenclamide attenuates the disruption of the BBB after ICH by inhibiting the activation of the NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike many other constitutively expressed SUR1 regulated channels in various systemic tissues, SUR1-TRPM4 is unique in that it is not normally present in the CNS, but undergoes de novo upregulation after CNS injury [36]. Upregulation of SUR1 with or without TRPM4 (hereafter SUR1±TRPM4) has been demonstrated in multiple CNS cell types (neurons, astrocytes, endothelial cells, macrophages, microglia) and models of injury, including ischemic stroke [56][57][58][59], TBI [50,[60][61][62], spinal cord injury (SCI) [63,64], intracerebral hemorrhage (ICH) [65], subarachnoid hemorrhage (SAH) [66,67], CNS metastases [68], cardiac arrest [69,70], hepatic failure [71], and encephalomyelitis [72][73][74] ( Figure 1A). The increased expression in several cell-types of the neurovascular unit renders SUR1-TRPM4 a likely contributor across the spectrum of cerebral edema endotypes (reviewed elsewhere [14,15,75]), including cellular/cytotoxic edema, ionic edema, vasogenic edema, and eventually hemorrhagic transformation/progression with complete disintegration of the BBB and oncotic death of endothelial cells ( Figure 1C) [14,15,76].…”
Section: Sur1-trpm4 Gli and Cerebral Edemamentioning
confidence: 99%
“…Therefore, prevention of SBI after ICH is very valuable . Studies on molecular mechanisms of SBI after ICH may provide new targets for the treatment of patients with ICH . Neuronal damage and apoptosis are important pathological process in SBI after ICH.…”
Section: Introductionmentioning
confidence: 99%